Bilateral Circumscribed Posterior Keratoconus: Visualization by Ultrasound Biomicroscopy and Slit-Scanning Topography Analysis - Robert Rejdak; Katarzyna Nowomiejska; Dariusz Haszcz; Anselm G. M. Jünemann (Journal of Ophthalmology)
This paper documents a rare nonprogressive developmental disorder—bilateral circumscribed posterior keratoconus—in a 60-year-old man referred for a cataract surgery. For the first time ultrasound biomicroscopy was used to visualise the local anterior bulging of the posterior corneal surface with concomitant thinning of the stroma. The amount of localized posterior depression, corneal thickness and the refractive power of both the posterior and anterior corneal curvature were measured using slit-scanning topography analysis (Orbscan).